When Health Care is Displaced by State Interests: Building Dialogue Through Shared Findings. (January 2019) - Sanders, Chris; Bisaillon, Laura
Health sociologists interested in how macro state influences affect micro health care practices have much to gain from meta-ethnography research. In this article, we bring together insights from two separate empirical studies on state health care services involving HIV/AIDS as a way to speak to larger issues about the organization and production of medical expertise and governance in health care systems. We use Noblit and Hare's meta-ethnography approach to bring these studies into conversation and identify six shared "organizers" of health care encounters. The organizers illustrate how state health interests operate across institutional contexts and impact the work of providers in seemingly unrelated health care settings. On the basis of this synthesis, we conclude that state interests both structure and create conflict in health care settings. We believe this perspective offers the potential to advance the goals of health sociology and the field of qualitative health research in general.